Young Higher Education Graduates in Portugal in the Context of Bologna Reform and Economic Crisis (2007-2012) - Suleman, F.; Figueiredo, M. C. T. (Workshop Youth in a Post-Crisis Europe: Regulatory Approaches and Their Perceptions, 2017)
Policy makers and higher education institutions have to address simultaneously the impacts of the Bologna process and the crisis on the employment of graduates in Portugal in the last decade. The country has reformed higher education in 2006 and is facing one of the most serious economic and financial crisis since 2008. This study uses Portuguese linked employer-employee data – “Quadros de Pessoal” to compare the job quality of young higher education graduates in 2007, before the crisis and immediately after the adoption of Bologna, and in 2012 at the peak of the crisis. Firstly, it is important to note the increasing number of graduates from 2007 to 2012. The statistics show that Portugal had an increase around 168% of undergraduates in this time frame. Alongside that, the overall unemployment rate was 8.0% in 2007 and 15.5% in 2012, while the unemployment rate of graduates was 7.4% and 11.6% respectively. The arising question is: how that supply affects job quality of graduates? And what is the impact of crisis? More specifically, this study examines the impact of types of contractual arrangement on wages and reassesses the labour market segmentation arguments in the context of higher education graduates. We combine two main characteristics of the contract notably flexibility vs stability, and working time, full time vs part-time. This leads to four arrangements which we labelled as Standard (stable and full-time), Underemployed (stable and part-time), Insecure (flexible and full-time), and Non-Standard (flexible and part-time). The goal is to ascertain which type of contract has the highest negative (positive) impact on wages and whether this impact has changed over time. Empirical findings suggest that stability benefits graduates whether they have full or part time contract. More importantly, Insecure contracts imply the highest wage penalisation for graduates. The findings show that graduates’ labour market is segmented and flexible contractual arrangements are the most precarious. Furthermore, labour market ranks graduates on the basis of field of education. Graduates from health, mathematic and statistics, and transport services earn higher wages. This pattern persists over time and shows that graduates from “hard” fields of education are privileged in the Portuguese labour market.